Mathematical methodology and MATLAB computer program to calculate the effective-dose of percent response using the probit analysis technique - Tlas, M (Computational ecology and software, 2023)
Using the probit analysis technique, mathematical algorithm and MATLAB computer program have been implemented in this paper to calculate both the Log-Dose (LD) and the Effective-Dose (ED) for any given percent. The probit analysis uses a successive weighted simple linear regression of experimental or row data. The kind of row data obtained from the bioassays should be generally in percent response (mortality or affected) at the corresponding doses (or concentrations). The response should be always in binomial form (e.g. death/no death) and the relationship between the response and the various doses or concentrations is always sigmoid or non-linear. The probit analysis here acts as a transformation from sigmoid or non-linear relationship to linear one and then uses a successive weighted simple linear regression on the linear relationship of the observed data. It is necessarily to note that, the probit analysis always assumes that the relationship between number responding (not proportion response) and dose (or concentration) should be normally distributed. Two simple examples are explained in this paper to prove the validity and the consistency of both the proposed mathematical methodology and the concerning computer program.